PROVISION OF ASYLUM FOR REFUGEE VICTIMS OF CONFLICT WITH ARMED ACCORDING TO INTERNATIONAL LAW AND ISLAMIC LAW - Mirsa Astuti (Proceeding International Seminar of Islamic Studies, 2022)
When there is an armed conflict between one country and another, the civilian population is a group of people who are always victims and therefore must receive protection. In this condition, sometimes they have to cross their national borders to get protection. Sometimes they are accommodated in a refugee camp provided by a neighboring country and there are also those who seek asylum individually to other countries. Several international bodies were then formed and during the United Nations era the International Refugee Organization (IRO) was formed with the mandate to protect refugee groups, which was later replaced by UNHCR (United Nations High Commissioner for Refugees). It is also tasked with leading and harmonizing international actions to protect refugees and solve refugee-related problems around the world. Islam grants asylum to anyone who requests it, regardless of religion, nationality or economic status. Islam protects the human rights of every human being without any discrimination. Islam views humans as equal, both in terms of rights, obligations and responsibilities. The difference in human degrees according to Islam is measured by one's piety. Islamic Shari'ah treats the principle of equality in the application of laws and regulations.Keywords: International Law, Islamic Law, Refugees, Asylum